2007
DOI: 10.1111/j.1751-2409.2007.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

Ageism: A Review of Research and Policy Implications

Abstract: The current literature on aging and ageism is summarized in support of a theoretical perspective that includes both the biological and the psychosocial components of these processes. Conceptual and methodological problems are identified in models that rely on a deficit approach to aging. We suggest that the biased responses of others foster older adults' stress‐related emotional and hormonal responses—responses that may effectively reduce their social and cognitive competence. This negative feedback process ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 143 publications
(159 reference statements)
3
69
1
3
Order By: Relevance
“…For instance, the effects that we observed may depend on whether people are focused more on the negative stereotypes of the elderly (weak, incompetent) than the positive stereotypes (friendly, warm; Cuddy, Norton, & Fiske, 2005). Finally, our participants were drawn from a Western, individualistic society where ageism may be more prevalent (but see Bugental & Hehman, 2007). On the basis of justice motive theory, we would predict that any characteristic of the victim or observer that leads to a more positive evaluation of an older victim (e.g., individuating information) would produce corresponding increases in perceived injustice and increases in punishment.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For instance, the effects that we observed may depend on whether people are focused more on the negative stereotypes of the elderly (weak, incompetent) than the positive stereotypes (friendly, warm; Cuddy, Norton, & Fiske, 2005). Finally, our participants were drawn from a Western, individualistic society where ageism may be more prevalent (but see Bugental & Hehman, 2007). On the basis of justice motive theory, we would predict that any characteristic of the victim or observer that leads to a more positive evaluation of an older victim (e.g., individuating information) would produce corresponding increases in perceived injustice and increases in punishment.…”
Section: Discussionmentioning
confidence: 90%
“…From patronizing speech (Nussbaum, Pitts, Huber, Raup Krieger, & Ohs, 2005) and social exclusion (Hagestad & Uhlenberg, 2005) to direct discrimination against older persons across a variety of domains (e.g., in the workplace and healthcare; e.g., Finkelstein & Farrell, 2007;Luker, Wall, Bernhardt, Edwards, & Grimmer-Somers, 2011), a growing literature has documented the negative effects of ageism. Nevertheless, although "getting old" is an eventual fate for most people, ageism is still a comparatively understudied "ism" in the psychological literature (Bugental & Hehman, 2007;Nelson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These clues, dubbed social affordances, may cause children, for instance, to learn that the wrinkles or slow gait in an older person signify someone who is not enthusiastic or outgoing (Palmore, 2003). Each of these theories highlights the idea that older people may be devalued simply from having more repellent bodily “blemishes” than the average person; these uncontrollable, highly visible characteristics undoubtedly devalue older people, paralleling other types of stigma as a marked status (Bugental & Hehman, 2007; Crocker, Major, & Steele, 1998; Jones et al, 1984). …”
Section: Extant Social-psychological Theories Used To Explain Ageismmentioning
confidence: 99%
“…Despite this universality, surprisingly scant research examines age-based prejudice, compared with racism and sexism (Nelson, 2004; 2005). Indeed, a quick PsycInfo search (February 2012) yields 8491 entries with the keyword “racism” and 2836 for “sexism,” but only 750 for “ageism.” Bugental and Hehman (2007) demonstrated the problem to be even more apparent when restricting the search to two of the premier social psychology journals; in the 20 years prior to their search, only one article on ageism appeared, compared with 50 and 33 respectively for racism and sexism. Some researchers have attempted to explain this lack of research focus by citing the socially-condoned nature of ageism, causing it to be overlooked altogether as a form of prejudice (Nelson, 2005; Palmore, 1999).…”
mentioning
confidence: 99%
“…Two research studies (Bugental & Hehman, 2007;Cuddy, Norton, & Fiske, 2005) suggested that in relation to age, both positive and negative stereotypes exist. Namely, that while elderly people are considered to be friendlier and warm, they are also perceived as being weak and incompetent.…”
Section: Social Stigma: Prejudice In Age and Gendermentioning
confidence: 99%